Structural effects of diamines on synthesis, polymerization, and properties of benzoxazines based on o-allylphenol. (28th January 2015) - Liu, Yanfang; Hao, Zhanzhan; Lv, Shufang; Huang, Jinbai; Liao, Chunyan; Run, Mingtao
Abstract: Two allyl-containing bifunctional benzoxazines ( o AP-hda and o AP-dds) were synthesized from o -allylphenol, formaldehyde, and two diamines [1, 6-hexamethylenediamine (HDA) and 4, 4′-diaminodiphenyl sulfone (DDS)]. The chemical structures of o AP-hda and o AP-dds were confirmed by 1 H and 13 C nuclear magnetic resonance (NMR) spectroscopy and Fourier transform infrared (FTIR) spectroscopy. The reactivity of HDA is higher than that of DDS in the synthetic reaction of benzoxazines, and the polymerization temperature of o AP-hda is lower than that of o AP-dds. The structure changes from benzoxazines to their corresponding polybenzoxazines [Poly( o AP-hda) and Poly( o AP-dds)] were studied by FTIR and solid state 13 C NMR. The dynamic mechanical properties and thermal stabilities of Poly( o AP-hda) and Poly( o AP-dds) were studied by dynamic mechanical analysis and thermogravimetry, respectively. The storage moduli in the glassy state are 1.44 and 3.18 GPa for Poly( o AP-hda) and Poly( o AP-dds), respectively, and the glass transition temperatures are 87 and 193 °C, respectively. The thermal stability of Poly( o AP-dds) is much higher than that of Poly( o AP-hda). Graphical abstract: Highlights: Two allyl-containing bifunctional benzoxazines were synthesized. The reactivity of HDA is higher than that of DDS. The polymerization temperature of o AP-hda is lower than that of o AP-dds. The T g of Poly( o AP-dds) is higher than that of Poly( o AP-hda).